Tectonic Structure and Relationship with Sinkhole Harzard in Bang Lung Area, Cho Don District, Bac Kan Province - Van Thom, Bui; Quoc Cuong, Tran; Hop phong, Lai; Trung Hieu, Tran; Duc Anh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 2, 2021)
By integration of remote sensing images analysis, geology, geomorphology, hydrogeology, geophysical method, and drilling data, the paper illustrates the structure tectonics, causes, and initial mechanism of a sinkhole forming in Bang Lung, Cho Don, Bac Kan province. The NE-SW normal slip faults are an essential fault system in the area, which created Bang Lung graben valley. This fault system also forms large fracture zones, creating advantage conditions for the groundwater runoff both vertically and horizontally to eroded and dissolved carbonate rock-forming underground karst caves. These are favorable natural conditions for forming a sinkhole. The sinkhole hazard in the Bang Lung area is initiated by some main factors such as tectonic activity, thickness, and characteristics of unconsolidated sediment layers, groundwater fluctuation, karst caves, and human activities. The most human impacts are mining exploitation and agricultural cultivation that promote sinkholes occurring faster and earlier. The horizontal and vertical movement of groundwater dragged the material on the ceiling karst caves into ground spaces. Thereby, weakening the cohesion of the unconsolidated sediment above caves leads to gravitational unbalance and creates a sinkhole. This study has also shown potential sinkhole areas in Bang Lung, which helps the authorities and local people in sinkhole prevention and mitigation mission.